2005
DOI: 10.1111/j.1523-1755.2005.09918.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α gene expression in diabetic nephropathy: Relationship with urinary albumin excretion and effect of angiotensin-converting enzyme inhibition

Abstract: DN was associated with increased renal expression of TNF-alpha and UAE. Enalapril administration prevented this enhanced expression of TNF-alpha and decreased urinary cytokine excretion and albuminuria. These data provide a novel insight into the pathogenic mechanisms of DN, and support the hypothesis that inflammatory mechanisms may play a significant role in the development and progression of renal injury secondary to diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 35 publications
5
97
0
3
Order By: Relevance
“…86 Experimental studies have consistently reported that mRNA encoding TNF-␣ and protein levels increase in glomerular and proximal tubule cells from diabetic rats. 45,73,74,[87][88][89] These investigations demonstrated a significant role of TNF-␣ in the development of renal hypertrophy and hyperfunction, two main alterations during the initial stage of diabetic nephropathy. 88,89 TNF-␣ has a stimulatory effect on sodium-dependent solute uptake in cultured mouse proximal tubular cells, 90 and in those studies diabetic rats exhibited enhanced urinary TNF-␣ excretion, sodium retention, and renal hypertrophy, which were prevented by administration of the anti-TNF-␣ agent TNFR:Fc, a soluble TNF-␣ receptor fusion protein.…”
Section: Tnf-␣mentioning
confidence: 99%
“…86 Experimental studies have consistently reported that mRNA encoding TNF-␣ and protein levels increase in glomerular and proximal tubule cells from diabetic rats. 45,73,74,[87][88][89] These investigations demonstrated a significant role of TNF-␣ in the development of renal hypertrophy and hyperfunction, two main alterations during the initial stage of diabetic nephropathy. 88,89 TNF-␣ has a stimulatory effect on sodium-dependent solute uptake in cultured mouse proximal tubular cells, 90 and in those studies diabetic rats exhibited enhanced urinary TNF-␣ excretion, sodium retention, and renal hypertrophy, which were prevented by administration of the anti-TNF-␣ agent TNFR:Fc, a soluble TNF-␣ receptor fusion protein.…”
Section: Tnf-␣mentioning
confidence: 99%
“…In the present study, the results showed that the pro-inflammatory cytokines TNF-α, IL-1β and IL-6 were notably decreased in SIRT4-overexpressing podocytes with glucose stimulation. TNF-α plays an important role in the development and progression of diabetic nephropathy supported by the observation of increases in renal TNF-α levels in diabetic animal models and patients (37,38), indicating that increased TNF-α levels result in renal damage. Clinical studies have reported significant increases in the renal production of IL-1β and IL-6 in patients with type 2 diabetic nephropathy compared with that in diabetic patients without nephropathy, suggesting a role of IL-1β and IL-6 in the pathogenesis of diabetic nephropathy (39,40).…”
mentioning
confidence: 94%
“…All these data suggest that the effect of chronic irbesartan treatment on the glomerular expression of VEGF and also proteinuria may be, at least in part, a BP independent mechanism. In STZ-induced diabetic rats, TNF-α content is increased in renal interstitial fluid, urine 15,17,38 and in glomeruli. 39,40 Although its role in diabetic nephropathy has not been extensively studied, Kalantarinia et al have related urinary and interstitial renal fluid TNF-α content to the development of microalbuminuria in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…15 The relationship between the RAS and renal interstitial fluid content or renal cortical RNA content of TNF-α has been studied in diabetic rats. 17,38 In those studies the chronic treatment with the ARBs/ACE-inhibitors reduced the renal interstitial fluid TNF-α or renal cortical TNF-α RNA content and the concomitant microalbuminuria. 17,38 Moreover, in a model of Ang II induced renal damage, using double transgenic rats harbouring human renin and angiotensinogen genes, the chronic treatment with a soluble TNF-α receptor antagonist (etanercept) reduced microalbuminuria in absence of any pressure effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation